Every Love Story Is a Ghost Story : A Life of David Foster Wallace - Max, D. T. (Daniel T.) (New York : Viking, 2012)
"The first biography of the renowned American author David Foster Wallace. Wallace was one of the most innovative and influential authors of the last twenty-five years. A writer whose distinctive style and example had a huge impact on the culture and helped give meaning to his generation in a disorienting, distressing time. In this first in-depth biography, journalist D.T. Max captures Wallace's compelling, turbulent life and times--his genius, his struggle to stay sane and happy in a difficult world, his anxiety and loneliness--as well as why he mattered as a writer and a human being"--.
Includes bibliographical references (p. 327-343) and index.
Keywords: Wallace, David Foster; Novelists, American -- 20th century -- Biography; BIOGRAPHY & AUTOBIOGRAPHY / Literary